The Making of Princeton University : From Woodrow Wilson to the Present - Axtell, James (Book collections on Project MUSE., 2006)
Publisher description: In 1902, Professor Woodrow Wilson took the helm of Princeton University, then a small denominational college with few academic pretensions. But Wilson had a blueprint for remaking the too-cozy college into an intellectual powerhouse. The Making of Princeton University tells, for the first time, the story of how the University adapted and updated Wilson's vision to transform itself into the prestigious institution it is today. James Axtell brings the methods and insights from his extensive work in ethnohistory to the collegiate realm, focusing especially on one of Princeton's most distinguished features: its unrivaled reputation for undergraduate education. Addressing admissions, the curriculum, extracurricular activities, and the changing landscape of student culture, the book devotes four full chapters to undergraduate life inside and outside the classroom. The book is a lively warts-and-all rendering of Princeton's rise, addressing such themes as discriminatory admission policies, the academic underperformance of many varsity athletes, and the controversial "bicker" system through which students have been selected for the University's private eating clubs. Written in a delightful and elegant style, The Making of Princeton University offers a detailed picture of how the University has dealt with these issues to secure a distinguished position in both higher education and American society. For anyone interested in or associated with Princeton, past or present, this is a book to savor.